(untitled) (Bangladesh Pharmaceutical Journal, 2012)
Methicillin-resistant Staphylococcus aureus (MRSA), resistant to all antibiotics including vancomycin, has been reported in Japan, USA, Canada and Brazil. Hence, the main objective of this study was to evaluate the possible presence of vancomycin resistant or intermediate Stap. aureus in Dhaka. A total of 122 clinical isolates were collected from different hospitals, clinics and diagnostic centers of the city for about 12 months starting from August 2010 to July 2011.They were identified using standard bacteriological methods. Sensitivity to recommended antibiotics was determined by disc diffusion method. In the present study 74% of total isolates were found to be betalactamase producers by iodometric methods, whereas with Nitrocefin® sticks 80% of the isolates were found to be beta-lactamase producers. All the multiple drug resistant strains were beta-lactamase producers. Out of 122 isolates, although no strains were found vancomycin resistant, 93.44% were found intermediate and only 6.56% showed sensitivity. This study reveals the growing antimicrobial resistance in Bangladesh and refers not to use the antimicrobial drugs that show insufficient sensitivity against Stap. aureus to prevent resistance and associated treatment failure. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12582 Bangladesh Pharmaceutical Journal 15(2): 159-163, 2012